ERROR ANALYSIS ON ENGLISH SOUND PRODUCED BY ENGLISH LEARNERS: THE INFLUENCE OF TRANSFER - Muflihah Islamiyah (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2012)
Second language acquisition has become a big issue in recent years and it leads to the study of transfer. As there are many problems faced by the lecturers deal with the students’ pronunciation, then this pa-per is aimed at revealing and describing the errors in pronouncing English sounds made by the English learners because of the negative transfer from their first language (L1). Mix method was used in this study, it began with the qualitative one and then to know the percentage of each data, quantitative one was applied. The data were got from the recording of speaking activities and interview and then it was transcribed into broad transcription. This study does not include the narrow transcription, therefore no suprasegmental features found in this paper. The results of this study revealed that most of the students made some errors in pronouncing English sounds which they cannot found in their first language such as the sound /æ/, /∫/, /θ/, /ð/, and /ʒ/. The result is hoped to be able to give some input to the English teacher and lecturer on the common errors made by the students in pronouncing English sounds and lead them to improve their teaching methods in order to help their students in pronouncing new sounds found in the target language. Keywords: Error, language transfer